DAUN KOPASANDA SEBAGAI TANAMAN ALTERNATIF PENANGKAL RADIKAL BEBAS - St. Maryam; Widyawati Widyawati; Uni Angreni Putri; Dian Lestari (Universitas Islam Negeri Alauddin Makassar, 2021)
Kopasanda leaves (Chromolaena folium) are rich in flavonoids, including polyphenolic compounds that are closely related as substances that have the antioxidant capacity to ward off free radicals. Polyphenols in kopasanda include catechins, epicatechins, procyanidins and anthocyanidins. Kopasanda contains total phenols and a higher antioxidant capacity than wine or tea. So it is said that Kopasanda has high levels of antioxidants. The total antioxidant potential of the sample is determined by the ability to reduce iron (Fe) as a measure of